Method for producing positive electrode active material, positive electrode active material, and battery
By ion-exchanging Na-containing oxide particles to form Li-containing oxide particles with controlled structures and compositions, the method addresses high resistance and rate characteristics issues in conventional O2 structures, enhancing performance in both solid and liquid batteries.
Patent Information
- Application Number
- JP2023113928
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-11
AI Technical Summary
Conventional positive electrode active materials with O2 structures exhibit high resistance in solid batteries and room for improvement in rate characteristics in liquid batteries.
The method involves manufacturing Li-containing oxide particles with a hollow single-layer or multilayer structure by ion-exchanging Na-containing oxide particles with a P2 structure to achieve an O2 structure, using spherical particles with controlled particle diameters and specific chemical compositions, including elements like Mn, Ni, and Co, to enhance performance.
The resulting Li-containing oxide particles demonstrate low resistance and improved rate characteristics when used in solid and liquid batteries, respectively, due to controlled crystallite growth and increased surface area for ion conduction.
Smart Images

Figure 2025011682000001_ABST
Abstract
Description
[Technical field]
[0001] The present application discloses a method for producing a positive electrode active material, a positive electrode active material, and a battery. [Background technology]
[0002] Positive electrode active materials having an O2 type structure are known. As disclosed in Patent Document 1, a positive electrode active material having an O2 type structure is obtained by ion-exchanging at least a part of Na in a Na-containing oxide having a P2 type structure with Li. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2011-170994 A Summary of the Invention [Problem to be solved by the invention]
[0004] Conventional positive electrode active materials having an O2 type structure have room for improvement in terms of resistance when applied to solid-state batteries, or in terms of rate characteristics when applied to liquid batteries. [Means for solving the problem]
[0005] The present application discloses the following aspects as means for solving the above problems. <Aspect 1> A method for producing a positive electrode active material for use in a solid-state battery, comprising: Obtaining Na-containing oxide particles having a P2 type structure, and and ion-exchanging at least a portion of the Na in the Na-containing oxide particles with Li to obtain Li-containing oxide particles having an O2 type structure. The Na-containing oxide particles are spherical particles having an average particle size of 1.0 μm or more and less than 3.5 μm, The Li-containing oxide particles are spherical particles having a hollow single-layer structure. Manufacturing method. <Aspect 2> The method for producing aspect 1, The Na-containing oxide particles contain, as constituent elements, at least one element selected from Mn, Ni, and Co, Na, and O. Manufacturing method. <Aspect 3> A positive electrode active material for use in a solid-state battery, comprising Li-containing oxide particles, The Li-containing oxide particles have an O2 type structure, the Li-containing oxide particles are spherical particles having a hollow single-layer structure, The Li-containing oxide particles have an average particle size of 1.0 μm or more and less than 3.5 μm. Cathode active material. <Aspect 4> The positive electrode active material of Aspect 3, The Li-containing oxide particles have a diameter of 4.5 m 2 / g specific surface area, Cathode active material. <Aspect 5> The positive electrode active material of aspect 3 or 4, The Li-containing oxide particles contain, as constituent elements, at least one element selected from Mn, Ni, and Co, Li, and O. Cathode active material. <Aspect 6> A solid-state battery having a positive electrode active material layer, an electrolyte layer, and a negative electrode active material layer, the positive electrode active material layer includes the positive electrode active material of any one of aspects 3 to 5, The positive electrode active material layer contains a solid electrolyte. solid state battery. <Aspect 7> A method for producing a positive electrode active material for use in a liquid battery, comprising the steps of: Obtaining Na-containing oxide particles having a P2 type structure, and and ion-exchanging at least a portion of the Na in the Na-containing oxide particles with Li to obtain Li-containing oxide particles having an O2 type structure. The Na-containing oxide particles are spherical particles having an average particle size of 3.5 μm or more, The Li-containing oxide particles are spherical particles having a hollow multilayer structure. Manufacturing method. <Aspect 8> The method of production of embodiment 7, The Na-containing oxide particles contain, as constituent elements, at least one element selected from Mn, Ni, and Co, Na, and O. Manufacturing method. <Aspect 9> A positive electrode active material for use in a liquid battery, comprising Li-containing oxide particles, The Li-containing oxide particles have an O2 type structure, the Li-containing oxide particles are spherical particles having a hollow multi-layer structure, The Li-containing oxide particles have an average particle size of 3.5 μm or more. Cathode active material. <Aspect 10> The positive electrode active material of embodiment 9, The Li-containing oxide particles have a diameter of 4.5 m 2 / g or more specific surface area, Cathode active material. <Aspect 11> The positive electrode active material of aspect 9 or 10, The Li-containing oxide particles contain, as constituent elements, at least one element selected from Mn, Ni, and Co, Li, and O. Cathode active material. <Aspect 12> A liquid battery having a positive electrode active material layer, an electrolyte layer, and a negative electrode active material layer, The positive electrode active material layer includes the positive electrode active material of any one of aspects 9 to 11, The positive electrode active material layer contains a liquid electrolyte. Liquid battery. Effect of the Invention
[0006] The positive electrode active material of the present disclosure has low resistance when applied to a solid-state battery, or has excellent rate characteristics when applied to a liquid battery. [Brief description of the drawings]
[0007] [Figure 1A] 1 shows an example of a flow of a method for producing a positive electrode active material used in a solid-state battery. [Figure 1B] 1 shows an example of a process for producing a positive electrode active material used in a liquid battery. [Figure 2A] 1 shows a schematic cross-sectional shape of a spherical particle having a hollow single-layer structure. [Figure 2B] 1 shows a schematic cross-sectional shape of a spherical particle having a hollow multi-layer structure. [Figure 2C] 1 shows a schematic cross-sectional shape of a spherical particle having a hollow multi-layer structure. [Diagram 3] 1 shows a schematic diagram of an example of a battery configuration. [Figure 4] The cross-sectional shapes of positive electrode active materials A to D are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] 1.First form The positive electrode active material according to the first embodiment is used in a solid-state battery.
[0009] 1.1 Manufacturing method of positive electrode active material used in solid-state batteries As shown in FIG. 1A, a method for producing a positive electrode active material for use in a solid-state battery includes the following steps: Obtaining Na-containing oxide particles having an S1:P2 type structure, and S2: Ion-exchanging at least a portion of the Na in the Na-containing oxide particles with Li to obtain Li-containing oxide particles having an O2 type structure. Here, the Na-containing oxide particles are spherical particles having an average particle size of 1.0 μm or more and less than 3.5 μm, and as shown in FIG. 2A, the Li-containing oxide particles are spherical particles having a hollow single-layer structure.
[0010] In this application, unless otherwise specified, the term "average particle size" refers to the particle size at an integrated value of 50% (D50, median size) in the volume-based particle size distribution determined by a laser diffraction / scattering method.
[0011] In the present application, "spherical particles" refers to particles having a circularity of 0.80 or more. The circularity of the spherical particles may be 0.81 or more, 0.82 or more, 0.83 or more, 0.84 or more, 0.85 or more, 0.86 or more, 0.87 or more, 0.88 or more, 0.89 or more, or 0.90 or more. The circularity of the particles is 4πS / L 2 Here, S is the orthogonal projected area of the particle, and L is the perimeter of the orthogonal projected image of the particle. The circularity of a particle can be determined by observing the appearance or cross-sectional shape of the particle using a scanning electron microscope (SEM), a transmission electron microscope (TEM), or an optical microscope. When a particle is composed of multiple particles, the circularity is measured, for example, as an average value as follows. (1) First, the particle size distribution of the particles is measured. Specifically, the particle size at 10% cumulative value (D10) and the particle size at 90% cumulative value (D90) in the volume-based particle size distribution are determined by a laser diffraction / scattering method. (2) Regarding the appearance of the particles whose particle size distribution has been measured, images are observed using a SEM, TEM, or optical microscope, and from the particles contained in the images, 100 particles having a circle equivalent diameter (the diameter of a circle having the same area as the orthogonal projected area of the particle) equal to or greater than D10 and equal to or less than D90 as determined in (1) are randomly selected. (3) The circularity of each of the 100 extracted particles is determined by image processing, and the average value is regarded as the "circularity of the particle."
[0012] 1.1.1 S1 In S1, Na-containing oxide particles having a P2 type structure are obtained. Here, the Na-containing oxide particles obtained in S1 are spherical particles having an average particle size of 1.0 μm or more and less than 3.5 μm.
[0013] The Na-containing oxide particles having a P2 type structure, a predetermined average particle size, and a spherical shape can be prepared, for example, through the following steps S1-1, S1-2, and S1-3. S1-1: Obtaining precursor particles S1-2: Coating the surface of the precursor particles with a Na source to obtain composite particles. S1-3: Sintering the composite particles
[0014] In S1-1, precursor particles are obtained. The precursor particles include at least one element of Mn, Ni, and Co, for example. The precursor particles may include at least Mn, one or both of Ni and Co, or may include at least Mn, Ni, and Co. The precursor particles may be a salt including at least one element of Mn, Ni, and Co. For example, the precursor particles may be at least one of carbonate, sulfate, nitrate, and acetate. Alternatively, the precursor particles may be a compound other than a salt. For example, the precursor particles may be a hydroxide. The precursor particles may be a hydrate. The precursor particles may be a combination of a plurality of types of compounds. The precursor particles are spherical particles. The size of the precursor particles is determined according to the average particle diameter of the target Na-containing oxide particles.
[0015] In S1-1, a precipitate as the precursor particle may be obtained by a co-precipitation method using an ion source capable of forming a precipitate in an aqueous solution with transition metal ions and a transition metal compound containing at least one element of Mn, Ni, and Co. As a result, spherical particles are obtained as the precursor particle. The "ion source capable of forming a precipitate in an aqueous solution with transition metal ions" may be at least one selected from, for example, sodium salts such as sodium carbonate and sodium nitrate, sodium hydroxide, and sodium oxide. The transition metal compound may be the above salt or hydroxide containing at least one element of Mn, Ni, and Co. Specifically, in S1-1, the ion source and the transition metal compound may be prepared as solutions, and the respective solutions may be dropped and mixed to obtain a precipitate as the precursor particle. In this case, for example, water is used as the solvent. In this case, various sodium compounds may be used as the base, and an aqueous ammonia solution or the like may be added to adjust the basicity. In the case of the co-precipitation method, for example, an aqueous solution of a transition metal compound and an aqueous solution of sodium carbonate are prepared, and the respective aqueous solutions are dropped and mixed to obtain a precipitate as the precursor particle. Alternatively, the precursor particles can be obtained by a sol-gel method, and in particular, by a coprecipitation method, spherical particles can be efficiently obtained as the precursor particles.
[0016] In S1-1, the precursor particles may contain element M. Element M is at least one selected from B, Mg, Al, K, Ca, Ti, V, Cr, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W. These elements M have a function of stabilizing, for example, a P2 type structure or an O2 type structure. The method of obtaining precursor particles containing element M is not particularly limited. When the precursor particles are obtained by coprecipitation in S1-1, for example, an aqueous solution of a transition metal compound containing at least one of Mn, Ni, and Co, an aqueous solution of sodium carbonate, and an aqueous solution of a compound of element M are prepared, and each aqueous solution is dropped and mixed to obtain a precursor containing element M together with at least one element of Mn, Ni, and Co. Alternatively, element M may not be added in S1-1, and element M may be doped when Na-doping baking is performed in S1-2 and S1-3 described later.
[0017] In S1-2, the surface of the precursor particle obtained in S1-1 is coated with a Na source to obtain composite particles. The Na source may be a salt containing Na, such as carbonate or nitrate, or a compound other than a salt, such as sodium oxide or sodium hydroxide. In S1-2, the amount of the Na source coated on the surface of the precursor particle may be determined taking into account the amount of Na lost during the subsequent firing.
[0018] In S1-2, the coverage of the Na source on the surface of the precursor particle is not particularly limited. For example, in S1-2, the composite particle may be obtained by covering 40 area% or more, 50 area% or more, 60 area% or more, or 70 area% or more of the surface of the precursor particle with the Na source. Here, when the precursor obtained by S1-1 is a spherical particle, and the composite particle obtained by S1-2 is obtained by covering 40 area% or more of the surface of the precursor particle with the Na source, the Na-containing oxide particle having the P2 type structure is likely to become a spherical particle in S1-3 described later. If the coverage of the Na source is small, when the composite particle is fired, the P2 type crystal is likely to grow abnormally on the surface of the composite particle, and the Na-containing oxide particle is likely to become a plate-like particle. If the coverage of the Na source is large, when the composite particle is fired, the crystallites of the P2 type crystal are likely to become small, and the Na-containing oxide particle is likely to become a spherical particle corresponding to the shape of the precursor particle.
[0019] In S1-2, the method for coating the surface of the precursor particle with the Na source is not particularly limited. As described above, when 40% or more of the surface of the precursor particle is coated with the Na source, various methods can be used. For example, a tumbling fluidized coating method or a spray drying method can be used. That is, a coating solution in which a Na source is dissolved is prepared, and the coating solution is brought into contact with the surface of the precursor particle, and dried at the same time or after the contact. By adjusting the coating conditions (temperature, time, number of times, etc.), 40% or more of the surface of the precursor particle can be coated with the Na source.
[0020] In S1-2, the precursor particles may be coated with the M source together with the Na source. For example, in S1-2, the precursor particles obtained in S1-1, the Na source, and an M source containing at least one element M selected from B, Mg, Al, K, Ca, Ti, V, Cr, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W may be mixed to obtain composite particles. The M source may be, for example, a salt containing the element M, such as a carbonate or sulfate, or a compound other than a salt, such as an oxide or hydroxide. The amount of the M source relative to the precursor particles may be determined according to the chemical composition of the Na-containing oxide particles after firing.
[0021] In S1-3, the composite particles obtained in S1-2 are fired to obtain a Na-containing oxide having a P2 type structure. S1-3 may include, for example, the following S1-3-1, S1-3-2, and S1-3-3. S1-3-1: Pre-firing the composite particles at a temperature of 300° C. or more and less than 700° C. for 2 hours or more and 10 hours or less. S1-3-2: Following the preliminary firing, the composite particles are subjected to a main firing at a temperature of 700° C. or more and 1100° C. or less for 30 minutes or more and 48 hours or less. S1-3-3: Following the main sintering, the composite particles are heated to a temperature T 1 Temperature T below 100°C 2 Rapid cooling until
[0022] In S1-3-1, the composite particles are pre-fired at a temperature of 300° C. or more and less than 700° C. for 2 hours or more and 10 hours or less. In S1-3-1, the composite particles may be formed as desired and then pre-fired. The pre-fire is performed at a temperature lower than that of the main firing. By performing the pre-fire sufficiently, the P2 phase can be appropriately generated in the main firing and the generation of crystal phases other than the P2 phase can be suppressed. That is, in S1-3-1, the pre-fire temperature is 300° C. or more and less than 700° C., and the pre-fire time is 2 hours or more and 10 hours or less, so that the composite particles can be pre-fired sufficiently, and the P2 phase can be appropriately generated in the Na-containing oxide particles obtained through S1-3-2 and S1-3-3 described later and the generation of phases other than the P2 phase can be suppressed. As a result, the Li-containing oxide particles obtained through S2 have an O2 type structure, a hollow single-layer structure, and are spherical. The pre-firing temperature may be 400° C. or more and less than 700° C., 450° C. or more and less than 700° C., 500° C. or more and less than 700° C., 550° C. or more and less than 700° C., or 550° C. or more and less than 650° C. The pre-firing time may be 2 hours or more and less than 8 hours, 3 hours or more and less than 8 hours, 4 hours or more and less than 8 hours, 5 hours or more and less than 8 hours, or 5 hours or more and less than 7 hours. The pre-firing atmosphere is not particularly limited, and may be, for example, an oxygen-containing atmosphere.
[0023] In S1-3-2, following the above pre-firing, the composite particles are subjected to main firing at a temperature of 700°C to 1100°C for 30 minutes to 48 hours. In S1-3-2, the main firing temperature of the composite particles is 700°C to 1100°C, preferably 800°C to 1000°C. If the main firing temperature is too low, the P2 phase is not generated, and if the main firing temperature is too high, the O3 phase and the like are likely to be generated instead of the P2 phase. The temperature rise condition from the pre-firing temperature to the main firing temperature is not particularly limited. The main firing time may be 30 minutes to 48 hours as described above. However, the shape of the Na-containing oxide particles can be controlled by the main firing time. As described above, when the coverage rate of the Na source in the composite particles is 40 area % or more, when the composite particles are fired, P2 type crystals with small crystallites are likely to be formed on the surface. In S1-3-2, the P2 type crystals are grown along the surface of the particles so that one P2 type crystallite is connected to another P2 type crystallite, so that the shape of the Na-containing oxide particles corresponds to that of the precursor particles. For example, when the precursor particles are spherical particles, the Na-containing oxide particles also become spherical particles. If the firing time is too short, the generation of the P2 phase becomes insufficient. On the other hand, if the firing time is too long, the P2 phase grows excessively, and the Na-containing oxide particles become plate-like particles rather than spherical particles. As far as the inventors have confirmed, when the firing time is 30 minutes or more and 3 hours or less, spherical particles of the Na-containing oxide particles are easily obtained. The Na-containing oxide particles obtained after the firing may have a structure in which a plurality of crystallites are present on the surface and the crystallites are connected to each other.
[0024] In S1-3-3, following the main sintering, the composite particles (P2 type particles) after the main sintering are heated to a temperature T 1 Temperature T below 100°C 2 The above pre-baking and main baking are performed, for example, in a heating furnace. In step S1-3-3, for example, after the main baking of the composite particles is performed in the heating furnace, the inside of the heating furnace is heated to an arbitrary temperature T 1 Cool to the temperature T 1After this, the baked product is removed from the furnace and heated to any temperature T below 100°C. 2 Rapid cooling is performed outside the furnace until the temperature T 1 is any temperature above 200° C., and may be any temperature above 250° C. 2 is any temperature below 100°C, may be any temperature below 50°C, or may be the cooling end temperature. 1 from temperature T 2 During the cooling process, moisture is likely to penetrate between the layers of the P2 type structure due to atomic vibrations and molecular motion. When the composite particles (P2 type particles) are cooled after the main sintering process, it is considered that the amount of moisture that penetrates between the layers of the P2 type structure can be reduced by shortening the time during which the temperature is in the temperature range in which moisture is likely to penetrate (i.e., by cooling at a high speed). In this regard, in step S1-3-3, when the composite particles are cooled after the main sintering process, the amount of moisture that penetrates between the layers of the P2 type structure can be reduced by shortening the time during which the temperature is in the temperature range in which moisture is likely to penetrate (i.e., by cooling at a high speed). 1 Any temperature T below 100°C 2 The temperature is then cooled outside the furnace (e.g., in a dry atmosphere outside the furnace) until the temperature T 1 from temperature T 2 The cooling rate during the cooling process is high (e.g., 20°C / min or more) until the temperature reaches 100°C, moisture is less likely to penetrate between the layers of the P2 type structure, and the collapse of the P2 type structure can be suppressed. As a result, in S2 described below, Na can be efficiently ion-exchanged with Li, and the Li-containing oxide particles obtained through S2 have an O2 type structure, a hollow single-layer structure, and are spherical particles.
[0025] By the above method, spherical Na-containing oxide particles having a P2 type structure can be obtained.
[0026] The Na-containing oxide particles have at least a P2 type structure (belonging to space group P63mc) as a crystal structure. The Na-containing oxide particles may have a crystal structure other than the P2 type structure in addition to the P2 type structure. Examples of the crystal structure other than the P2 type structure include various crystal structures formed when Na is desorbed from the P2 type structure. The Na-containing oxide particles may have a P2 type structure as a main phase.
[0027] The Na-containing oxide particles contain, for example, as constituent elements, at least one element selected from Mn, Ni, and Co, Na, and O. In particular, when the constituent elements contain at least Na, Mn, at least one element selected from Ni and Co, and O, and especially when the constituent elements contain at least Na, Mn, Ni, Co, and O, the performance of the positive electrode active material obtained through S2 described below tends to be further improved. The Na-containing oxide particles contain Na c Mn x-p Ni y-q Co z-r M p+q+r O 2It may have a chemical composition represented by the following. Here, 0 < c ≤ 1.00, x + y + z = 1, and 0 ≤ p + q + r < 0.17. Also, M is at least one element selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W. When the Na-containing oxide particles have such a chemical composition, the P2-type structure is more likely to be maintained. In the above chemical composition, c may be greater than 0, 0.10 or more, 0.20 or more, 0.30 or more, 0.40 or more, 0.50 or more, or 0.60 or more, and may be 1.00 or less, 0.90 or less, 0.80 or less, or 0.70 or less. x is 0 or more, 0.10 or more, 0.20 or more, 0.30 or more, 0.40 or more, or 0.50 or more, and may be 1.00 or less, 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, or 0.50 or less. Also, y is 0 or more, 0.10 or more, or 0.20 or more, and may be 1.00 or less, 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, 0.30 or less, or 0.20 or less. Also, z is 0 or more, 0.10 or more, 0.20 or more, or 0.30 or more, and may be 1.00 or less, 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, or 0.30 or less. The contribution of element M to charge and discharge is small. In this regard, in the above chemical composition, since p + q + r is less than 0.17, a high charge-discharge capacity is likely to be ensured. p + q + r may be 0.16 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, or 0.10 or less. On the other hand, when element M is included, the P2-type structure and the O2-type structure are likely to be stabilized. In the above chemical composition, p + q + r is 0 or more, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, or 0.10 or more. The composition of O is approximately 2, but it is not necessarily exactly 2.0 and is indefinite.
[0028] In the first embodiment, in S2 described later, spherical particles having an average particle size of 1.0 μm or more and less than 3.5 μm are used as the Na-containing oxide particles. The spherical Na-containing oxide particles can be produced, for example, by producing composite particles using spherical precursor particles as described above and adjusting the firing conditions of the composite particles. Here, by using precursor particles having an average particle size of less than 3.5 μm and being spherical, Na-containing oxide particles having an average particle size of 1.0 μm or more and less than 3.5 μm and being spherical can be obtained. Alternatively, after producing spherical Na-containing oxide particles using precursor particles having random sizes, air flow classification, sieving, or the like may be performed to recover spherical Na-containing oxide particles having an average particle size of 1.0 μm or more and less than 3.5 μm.
[0029] The average particle size of the Na-containing oxide particles is 1.0 μm or more and less than 3.5 μm, and may be 1.2 μm or more and less than 3.3 μm, or 1.4 μm or more and less than 3.0 μm. When the average particle size of the Na-containing oxide particles is 1.0 μm or more and less than 3.5 μm, the Li-containing oxide particles obtained through S2 described below have a hollow single-layer structure. If the Na-containing oxide particles are too small, the Li-containing oxide particles do not have a hollow structure.
[0030] 1.1.2 S2 In S2, at least a part of the Na in the Na-containing oxide particles obtained in S1 is ion-exchanged with Li to obtain Li-containing oxide particles having an O2 type structure. Here, the Li-containing oxide particles obtained in S2 are spherical particles having a hollow single-layer structure.
[0031] In S2, the ion exchange can be performed, for example, by using an aqueous solution containing lithium halide or by using a mixture of lithium halide and other lithium salts (for example, molten salt). From the viewpoint that the P2 type structure is easily broken by the intrusion of water and from the viewpoint of crystallinity, the method using the molten salt is preferable among the above two methods. That is, by mixing the Na-containing oxide particles having the above-mentioned P2 type structure with the molten salt and heating the mixture to a temperature equal to or higher than the melting point of the molten salt, at least a part of the Na in the Na-containing oxide particles can be replaced with Li by ion exchange.
[0032] In S2, the lithium halide constituting the molten salt is preferably at least one of lithium chloride, lithium bromide, and lithium iodide. The other lithium salt constituting the molten salt is preferably lithium nitrate. By using the molten salt, the melting point becomes lower than when the lithium halide or other lithium salt is used alone, and ion exchange can be performed at a lower temperature.
[0033] In S2, the temperature in the ion exchange may be, for example, equal to or higher than the melting point of the molten salt and equal to or lower than 600°C, 500°C, 400°C, or 300°C. If the temperature in the ion exchange is too high, the stable O3 structure is likely to be formed instead of the O2 structure. On the other hand, from the viewpoint of shortening the time required for the ion exchange, it is preferable that the temperature in the ion exchange is as high as possible.
[0034] In S2, at least a part of Na in a spherical Na-containing oxide particle is ion-exchanged with Li, so that Na with a large ionic radius is replaced with Li with a small ionic radius, and the interlayer distance in the crystal structure is shortened, causing shrinkage. Such shrinkage during ion exchange creates voids inside the particle. When the size of the Na-containing oxide particle is small, the shrinkage creates voids in the center of the particle, resulting in a hollow single-layer structure. On the other hand, when the size of the Na-containing oxide particle is large, the shrinkage creates cracks in the circumferential direction inside the particle, resulting in a large number of "shells," resulting in a hollow multi-layer structure described later. Note that when the Na-containing oxide particle has a shape other than spherical, uniform shrinkage does not occur inside the particle, and an appropriate hollow structure cannot be obtained.
[0035] By the above method, Li-containing oxide particles having an O2 type structure, a hollow single-layer structure, spherical particles, and an average particle size of 1.0 μm or more and less than 3.5 μm can be obtained. The Li-containing oxide particles are used as a positive electrode active material for a solid-state battery.
[0036] 1.2 Positive electrode active materials used in solid-state batteries The positive electrode active material used in the solid-state battery according to the first embodiment includes Li-containing oxide particles. Here, the Li-containing oxide particles have an O2 type structure. As shown in FIG. 2A, the Li-containing oxide particles are spherical particles having a hollow single-layer structure. The Li-containing oxide particles have an average particle size of 1.0 μm or more and less than 3.5 μm.
[0037] 1.2.1 Crystal structure The Li-containing oxide particle according to the first embodiment has at least an O2 type structure (belonging to space group P63mc) as a crystal structure. The Li-containing oxide particle according to an embodiment has an O2 type structure and may have a crystal structure other than the O2 type structure. Examples of the crystal structure other than the O2 type structure include a T♯2 type structure (belonging to space group Cmca) formed when Li is deintercalated from the O2 type structure and an O6 type structure (belonging to space group R-3m, having a c-axis length of 2.5 nm to 3.5 nm, typically 2.9 nm to 3.0 nm, and different from the O3 type structure also belonging to space group R-3m). The Li-containing oxide particle according to an embodiment may have an O2 type structure as a main phase. The Li-containing oxide particle according to an embodiment may have a structure other than the O2 type structure (for example, an O6 type structure) as a main phase. The crystal structure of the Li-containing oxide particle as a main phase may change depending on the charge / discharge state.
[0038] 1.2.2 Crystallites The Li-containing oxide particle according to the first embodiment may be polycrystalline having a plurality of crystallites. For example, the Li-containing oxide particle according to one embodiment may have a surface formed of a plurality of crystallites. In other words, the Li-containing oxide particle may have a structure in which a plurality of crystallites are connected to each other on the surface. When the surface of the Li-containing oxide particle is formed of a plurality of crystallites, a crystal grain boundary is present on the surface. Here, the crystal grain boundary may be an inlet and an outlet of intercalation. That is, when the Li-containing oxide particle is polycrystalline having a plurality of crystallites, the effect of increasing the number of inlets and outlets of intercalation and decreasing the reaction resistance, the effect of shortening the moving distance of lithium ions and decreasing the diffusion resistance, the effect of reducing the absolute amount of expansion and contraction during charging and discharging and making it difficult for cracks to occur, etc. can be expected. The size of the crystallite may be large or small, but it is considered that the smaller the size of the crystallite, the more the crystal grain boundaries will be, and the more likely the above-mentioned advantageous effects will be exhibited. For example, when the diameter of the crystallite constituting the Li-containing oxide particle is less than 1 μm, higher performance is likely to be obtained. The "crystallite" and "diameter of the crystallite" can be determined by observing the surface of the Li-containing oxide particle with a scanning electron microscope (SEM) or a transmission electron microscope (TEM). That is, when the surface of the Li-containing oxide particle is observed and one closed region surrounded by the grain boundary is observed, the region is regarded as a "crystallite". The maximum Feret diameter of the crystallite is determined and regarded as the "diameter of the crystallite". Alternatively, the diameter of the crystallite can be determined by EBSD or XRD. For example, the diameter of the crystallite can be determined based on the Scherrer formula from the half-width of the diffraction line of the XRD pattern. When the diameter of the crystallite specified by any method is less than 1 μm, the Li-containing oxide particle is likely to exhibit higher performance. The crystallite constituting the Li-containing oxide particle may have a first surface exposed on the surface of the particle, and the first surface may be planar. That is, the surface of the Li-containing oxide particle may have a structure in which a plurality of planes are connected.As described above, when producing Li-containing oxide particles, crystallites having a planar first surface can be easily obtained by growing the crystallites on the surface of the particles until one crystallite and another crystallite are connected to each other.
[0039] 1.2.3 Chemical composition The Li-containing oxide particles according to the first embodiment contain, for example, as constituent elements, at least one element selected from Mn, Ni, and Co, Li, and O. The Li-containing oxide particles are particularly likely to achieve higher performance when they contain, as constituent elements, at least Li, Mn, one or both of Ni and Co, and O, and particularly when they contain, as constituent elements, at least Li, Mn, Ni, Co, and O. The Li-containing oxide particles contain Li. a Na b Mn x-p Ni y-q Co z-r M p+q+r O 2(Here, 0 < a ≤ 1.00, 0 ≤ b ≤ 0.20, x + y + z = 1, and 0 ≤ p + q + r < 0.17, and the element M is at least one selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W.) It may have a chemical composition represented by. When the Li-containing oxide particles have such a chemical composition, the O2-type structure is likely to be maintained. In the above chemical composition, a is greater than 0, and may be 0.10 or more, 0.20 or more, 0.30 or more, 0.40 or more, 0.50 or more, or 0.60 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, or 0.70 or less. In the above chemical composition, b is 0 or more, and may be 0.01 or more, 0.02 or more, or 0.03 or more, and is 0.20 or less, 0.15 or less, or 0.10 or less. Also, x is 0 or more, and may be 0.10 or more, 0.20 or more, 0.30 or more, 0.40 or more, or 0.50 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, or 0.50 or less. Also, y is 0 or more, and may be 0.10 or more or 0.20 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, 0.30 or less, or 0.20 or less. Also, z is 0 or more, and may be 0.10 or more, 0.20 or more, or 0.30 or more, and is 1.00 or less, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, or 0.30 or less. The element M has little contribution to charge and discharge. In this regard, in the above chemical composition, since p + q + r is less than 0.17, a high charge and discharge capacity is likely to be ensured. p + q + r may be 0.16 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, or 0.10 or less. On the other hand, when the element M is included, the O2-type structure is likely to be stabilized. In the above chemical composition, p + q + r is 0 or more, and may be 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, or 0.10 or more.)The composition of O is approximately 2, but is not necessarily exactly 2.0 and is variable.
[0040] 1.2.4 Hollow single layer structure The Li-containing oxide particle according to the first embodiment has a hollow single-layer structure. As shown in FIG. 2A, the "hollow single-layer structure" means a structure in which the cross-sectional shape of the particle has an outer shell 1a and the inside of the outer shell is hollow (void). The surface of the outer shell 1a may be composed of, for example, a plurality of crystallites. In the Li-containing oxide particle, the outer shell 1a may be composed of a plurality of crystallites connected along the outer periphery of the particle. The size of the crystallites constituting the outer shell 1a may be large or small, but the smaller the crystallite size, the more grain boundaries there are on the particle surface, and the more likely the above-mentioned advantageous effects are to be exhibited. In addition, the crystallites constituting the outer shell 1a may have a first surface exposed on the particle surface, and the first surface may be planar. The size of the crystallites is as described above. The outer shape (outer peripheral shape) of the outer shell 1a is spherical as described above. On the other hand, the inner shape (inner peripheral shape) of the outer shell 1a is not particularly limited, and may be a shape corresponding to the outer shape. However, the outer shape and the inner shape of the outer shell 1a do not need to be parallel to each other. Both the outer shape and the inner shape of the outer shell 1a may have irregularities. Furthermore, the outer shell 1a may have voids or gaps. That is, the crystallites constituting the outer shell 1a may have defects such as voids or gaps. Furthermore, the outer shell 1a may have a thickness. The thickness of the outer shell 1a may be, for example, 5% or more and less than 50% or 5% or more and 45% or less of the diameter (circle equivalent diameter in the cross-sectional shape) of the Li-containing oxide particle. The size of the voids present inside the outer shell 1a (porosity) is not particularly limited.
[0041] As shown in Fig. 2A, the Li-containing oxide particle according to the first embodiment can be said to have a core-shell structure. That is, the Li-containing oxide particle according to one embodiment can have a shell and a core (void) disposed inside the shell. The "shell" is as described above. On the other hand, the "core" may be entirely void.
[0042] 1.2.5 Spherical particles As described above, the Li-containing oxide particles having the O2 type structure are obtained by ion-exchanging at least a part of Na in the Na-containing oxide particles having the P2 type structure with Li. Here, the P2 type structure is a hexagonal crystal system, has a large diffusion coefficient of Na ions, and is prone to crystal growth in a specific direction. In particular, when at least one of Mn, Ni, and Co is included as a transition metal element constituting the P2 type structure, the crystal is prone to plate-like growth in a specific direction. Therefore, in the past, only plate-like ones with a large aspect ratio in which the crystal growth direction is biased in a specific direction could be produced as Na-containing oxide particles having the P2 type structure, and as a result, only plate-like ones could be produced for Li-containing oxide particles having the O2 type structure. In addition, the plate-like growth of the P2 type structure was considered to be a fundamental principle and unavoidable. Therefore, for the conventional O2 type Li-containing oxide particles, the performance as an active material was improved by controlling the chemical composition and crystal structure on the premise that they were plate-like.
[0043] In contrast, as shown in FIG. 2A, the Li-containing oxide particles according to the first embodiment are spherical particles. The spherical Li-containing oxide particles have the advantage that the growth of crystallites is easily suppressed and the crystallites are easily small, compared with non-spherical Li-containing oxide particles (for example, the above-mentioned plate-like particles). That is, when the Li-containing oxide particles are spherical, the reaction resistance is reduced due to the reduction in the crystallite size, and the internal diffusion resistance is easily reduced. Furthermore, it is considered that the degree of curvature is reduced by the spheroidization, and when applied to a positive electrode active material layer, the lithium ion conduction resistance in the layer is reduced. As a result, the spherical Li-containing oxide particles tend to have lower resistance and excellent rate characteristics, compared with non-spherical Li-containing oxide particles.
[0044] 1.2.6 Average particle size The Li-containing oxide particles according to the first embodiment have an average particle diameter of 1.0 μm or more and less than 3.5 μm. The average particle diameter of the Li-containing oxide particles may be 1.2 μm or more and 3.3 μm or less, or 1.4 μm or more and 3.0 μm or less. As described above, if the average particle diameter of the Li-containing oxide particles is 1.0 μm or more and less than 3.5 μm, the Li-containing oxide particles have a hollow single-layer structure, and have low resistance when applied to a solid-state battery. If the Li-containing oxide particles are too small, aggregation between the particles is likely to occur. If the average particle diameter of the Li-containing oxide particles is 1.0 μm or more, such aggregation problems are unlikely to occur.
[0045] 1.2.7 Specific surface area The specific surface area of the Li-containing oxide particles according to the first embodiment is not particularly limited. However, when it is assumed that the Li-containing oxide particles are used as a positive electrode active material of a solid-state battery, it is considered that the smaller the specific surface area of the Li-containing oxide particles, the fewer the voids and the like inside the Li-containing oxide particles, and the easier it is to ensure an ion conduction path. In this regard, when the Li-containing oxide particles have a hollow single-layer structure, are spherical particles, and have an average particle diameter of 1.0 μm or more and less than 3.5 μm, the Li-containing oxide particles are 4.5 μm or less. 2 When the Li-containing oxide particles have a specific surface area of less than 1.0 m / g, they can be expected to have higher performance as a positive electrode active material for solid-state batteries. 2 / g or more 4.5m 2 / g, less than 2.0m 2 / g or more 4.0m 2 / g or less, or 2.5m 2 / g or more 3.5m 2 / g or less.
[0046] 1.2.8 Supplementary Information The positive electrode active material according to the first embodiment may be composed of only the Li-containing oxide particles, or may contain other positive electrode active materials (other positive electrode active materials) together with the Li-containing oxide particles. From the viewpoint of further enhancing the effect of the technology of the present disclosure, the proportion of other positive electrode active materials in the entire positive electrode active material may be small. For example, the content of the Li-containing oxide particles may be 50% by mass or more and 100% by mass or less, 60% by mass or more and 100% by mass or less, 70% by mass or more and 100% by mass or less, 80% by mass or more and 100% by mass or less, 90% by mass or more and 100% by mass or less, 95% by mass or more and 100% by mass or less, or 99% by mass or more and 100% by mass or less, based on the entire positive electrode active material being 100% by mass.
[0047] 1.3 Solid state batteries The positive electrode active material according to the first embodiment is used as a positive electrode active material of a solid-state battery. The term "solid-state battery" refers to a battery containing a solid electrolyte. The solid-state battery may contain a liquid component together with the solid electrolyte, or may be an all-solid-state battery that does not contain a liquid component. The electrolyte contained in the solid-state battery may be all solid electrolytes, or may be a combination of a solid electrolyte and a liquid electrolyte. As shown in FIG. 3, a solid-state battery 100 according to one embodiment has a positive electrode active material layer 10, an electrolyte layer 20, and a negative electrode active material layer 30. Here, the positive electrode active material layer 10 contains the positive electrode active material according to the first embodiment. The positive electrode active material layer 10 contains a solid electrolyte.
[0048] 1.3.1 Cathode active material layer The positive electrode active material layer 10 includes at least the positive electrode active material according to the first embodiment and a solid electrolyte, and may further include other electrolytes, conductive assistants, binders, and the like. Furthermore, the positive electrode active material layer 10 may further include various additives. The content of each of the positive electrode active material, electrolyte, conductive assistant, binder, and the like in the positive electrode active material layer 10 may be appropriately determined according to the intended battery performance. For example, the content of the positive electrode active material may be 40% by mass or more, 50% by mass or more, or 60% by mass or more, and may be 100% by mass or less, or 90% by mass or less, with the entire positive electrode active material layer 10 (total solid content) being 100% by mass. The shape of the positive electrode active material layer 10 is not particularly limited, and may be, for example, a sheet-like positive electrode active material layer 10 having a substantially flat surface. The thickness of the positive electrode active material layer 10 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.
[0049] 1.3.1.1 Cathode active material The positive electrode active material is as described above. That is, the positive electrode active material layer 10 contains at least the Li-containing oxide particles as the positive electrode active material. As described above, the positive electrode active material may be composed of only the Li-containing oxide particles, or may contain other positive electrode active materials (other positive electrode active materials) together with the Li-containing oxide particles. From the viewpoint of further enhancing the effect of the technology of the present disclosure, the ratio of other positive electrode active materials to the entire positive electrode active material may be small. For example, the content of the Li-containing oxide particles may be 50% by mass or more and 100% by mass or less, 60% by mass or more and 100% by mass or less, 70% by mass or more and 100% by mass or less, 80% by mass or more and 100% by mass or less, 90% by mass or more and 100% by mass or less, 95% by mass or more and 100% by mass or less, or 99% by mass or more and 100% by mass or less.
[0050] Any other cathode active materials can be any of those known as cathode active materials for solid-state batteries. The other cathode active materials may be, for example, at least one selected from various lithium compounds other than the above-mentioned Li-containing oxides, elemental sulfur, sulfur compounds, and the like. The lithium compound as the other cathode active material may be a Li-containing oxide containing at least one element M, Li, and O. The element M may be, for example, at least one selected from Mn, Ni, Co, Al, Mg, Ca, Sc, V, Cr, Cu, Zn, Ga, Ge, Y, Zr, Sn, Sb, W, Pb, Bi, Fe, and Ti, or may be at least one selected from the group consisting of Mn, Ni, Co, Al, Fe, and Ti. More specifically, the Li-containing oxide as the other cathode active material is lithium cobaltate, lithium nickelate, lithium manganate, lithium nickel cobaltate, lithium nickel manganate, lithium cobalt manganate, lithium nickel cobalt manganate (Li 1±α Ni x Co y Mn z O 2±δ (for example, 0 < x < 1, 0 < y < 1, 0 < z < 1, x + y + z = 1)), spinel-type lithium compounds (Li 1+x Mn 2-x-y M y O 4 (M is one or more selected from Al, Mg, Co, Fe, Ni, and Zn), such as hetero-element-substituted Li-Mn spinel with a composition represented thereby), lithium nickel cobalt aluminum oxide (for example, Li 1±α Ni p Co q Al r O 2±δ (for example, p + q + r = 1)), lithium titanate, lithium metal phosphate (LiMPO 4and the like, M may be at least one selected from Fe, Mn, Co, and Ni). In particular, when the other positive electrode active material contains at least one of Ni, Co, and Mn as a constituent element, and a Li-containing oxide containing Li and O, the performance of the battery is more likely to be improved. Alternatively, when the other positive electrode active material contains at least one of Ni, Co, and Al as a constituent element, and a Li-containing oxide containing Li and O, the performance of the battery is more likely to be improved. Only one type of the other positive electrode active material may be used alone, or two or more types may be used in combination. The shape of the other positive electrode active material may be a general shape as a positive electrode active material for a battery. The other positive electrode active material may be, for example, particulate. The other positive electrode active material may be solid or may have voids, for example, porous or hollow. The other positive electrode active material may be primary particles, or may be secondary particles in which a plurality of primary particles are aggregated. The average particle diameter D50 of other positive electrode active materials may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less.
[0051] 1.3.1.2 Protection layer An ion-conductive protective layer may be formed on the surface of the positive electrode active material. That is, the positive electrode active material layer 10 may include a complex of the positive electrode active material and the protective layer, and at least a part of the surface of the positive electrode active material in the complex may be covered with the protective layer. This makes it easier to suppress, for example, the reaction between the positive electrode active material and other battery materials (such as the sulfide solid electrolyte described below). The ion-conductive protective layer may include various ion-conductive compounds. The ion-conductive compound may be, for example, at least one selected from ion-conductive oxides and ion-conductive halides.
[0052] The ion conductive oxide may contain, for example, at least one element selected from B, C, Al, Si, P, S, Ti, La, Zr, Nb, Mo, Zn, and W, Li, and O. The ion conductive oxide may be an oxynitride containing N. More specifically, the ion conductive oxide may contain Li 3 BO 3 , LiBO 2 , Li 2 CO 3 , LiAlO 2 , Li 4 SiO 4 , Li 2 SiO 3 , Li 3 PO 4 , Li 2 SO 4 , Li 2 TiO 3 , Li 4 Ti 5 O 12 , Li 2 Ti 2 O 5 , Li 2 ZrO 3 , LiNbO 3 , Li 2 MoO 4 , Li 2 WO 4 , LiPON, Li 2 O-LaO 2 , Li 2 O-ZnO 2 etc. The ion conductive oxide may be one in which some elements are substituted with various doping elements.
[0053] The ion conductive halide may be, for example, at least one of various compounds exemplified as the halide solid electrolyte described later. The ion conductive halide may include, for example, at least one element selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sn, Al, Sc, Ga, Bi, Sb, Zr, Hf, Ti, Ta, Nb, W, Y, Gd, Tb and Sm, at least one halogen element selected from the group consisting of Cl, Br, I and F, and Li. The ion conductive halide may include at least one element selected from the group consisting of Ti, Al, Gd, Ca, Zr and Y, at least one element selected from the group consisting of Cl, Br, I and F, and Li. The ion conductive halide may also include at least one element selected from the group consisting of Ti and Al, at least one element selected from the group consisting of Cl, Br, I and F, and Li. The ion conductive halide may also be, for example, a complex halide of Li, Ti, Al and F.
[0054] The coverage (area ratio) of the protective layer with respect to the surface of the positive electrode active material may be, for example, 70% or more, 80% or more, or 90% or more. The thickness of the protective layer may be, for example, 0.1 nm or more or 1 nm or more, and may be 100 nm or less, or 20 nm or less.
[0055] 1.3.1.2 Electrolytes The positive electrode active material layer 10 includes a solid electrolyte. As the solid electrolyte, a known one may be used. The solid electrolyte may be an inorganic solid electrolyte or an organic polymer electrolyte. In particular, the inorganic solid electrolyte is excellent in ion conductivity and heat resistance. Examples of the inorganic solid electrolyte include an oxide solid electrolyte, a sulfide solid electrolyte, and an ion-bonded inorganic solid electrolyte. Among the inorganic solid electrolytes, a sulfide solid electrolyte, and among them, a sulfide solid electrolyte containing at least Li, S, and P as constituent elements, has high performance. Alternatively, among the inorganic solid electrolytes, an ion-bonded solid electrolyte, and among them, a solid electrolyte containing at least Li, Y, and a halogen (at least one of Cl, Br, I, and F) as constituent elements, has high performance. The solid electrolyte may be amorphous or crystalline. The solid electrolyte may be particulate. The average particle diameter (D50) of the solid electrolyte may be, for example, 10 nm or more and 10 μm or less. The ion conductivity of the solid electrolyte at 25° C. is, for example, 1×10 -5 S / cm or more, 1×10 -4 S / cm or more, or 1×10 -3 The solid electrolyte may have a specific surface area of 100 nm or more and may have a specific surface area of 100 nm or more.
[0056] The oxide solid electrolyte is lithium lanthanum zirconate, LiPON, Li 1+X Al X Ge 2-X (PO 4 ) 3 , Li-SiO-based glass, Li-Al-SO-based glass, etc. In addition, when an oxide solid electrolyte is combined with a liquid electrolyte, ion conductivity can be improved.
[0057] The sulfide solid electrolyte may be a glass-based sulfide solid electrolyte (sulfide glass), a glass ceramic-based sulfide solid electrolyte, or a crystalline sulfide solid electrolyte. The sulfide glass is amorphous. The sulfide glass may have a glass transition temperature (Tg). In addition, when the sulfide solid electrolyte has a crystalline phase, examples of the crystalline phase include a Thio-LISICON type crystalline phase, a LGPS type crystalline phase, and an Argyrodite type crystalline phase. The sulfide solid electrolyte may be particulate. The average particle diameter (D50) of the sulfide solid electrolyte may be, for example, 10 nm or more and 100 μm or less.
[0058] The sulfide solid electrolyte may contain, for example, Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S element. The sulfide solid electrolyte may further contain at least one of O element and halogen element. The sulfide solid electrolyte may contain S element as a main component of anion element.
[0059] The sulfide solid electrolyte is, for example, Li 2 SP 2 S 5 , Li 2 SP 2 S 5 - LiI, Li 2 SP 2 S 5 -GeS 2 , Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 SP 2 S 5 -LiI-LiBr, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -LiBr, Li2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S 5 - LiI, Li 2 S.B. 2 S 3 , Li 2 SP 2 S 5 -ZmSn (where m and n are positive numbers. Z is Ge, Zn, or Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (wherein x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In).
[0060] The composition of the sulfide solid electrolyte is not particularly limited, but may be, for example, xLi 2 S·(100-x)P 2 S 5 (70≦x≦80), yLiI・zLiBr・(100-yz)(xLi 2 S (1-x)P 2 S 5 ) (0.7≦x≦0.8, 0≦y≦30, 0≦z≦30) and the like. Alternatively, the sulfide solid electrolyte may be represented by the general formula: Li 4-x Ge 1-x P x S 4It may have a composition represented by (0 < x < 1). In the above general formula, at least a part of Ge may be substituted with at least one of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. In the above general formula, at least a part of P may be substituted with at least one of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. In the above general formula, a part of Li may be substituted with at least one of Na, K, Mg, Ca, and Zn. In the above general formula, a part of S may be substituted with a halogen (at least one of F, Cl, Br, and I). Alternatively, the sulfide solid electrolyte is Li 7-a PS 6-a X a (X is at least one of Cl, Br, and I, and a is a number of 0 or more and 2 or less) and may have a composition represented thereby. a may be 0, or may be greater than 0. In the latter case, a may be 0.1 or more, may be 0.5 or more, or may be 1 or more. Also, a may be 1.8 or less, may be 1.5 or less.
[0061] The ion-bonded solid electrolyte may contain at least one element selected from the group consisting of, for example, Mg, Ca, Sr, Ba, Zn, Sn, Al, Sc, Ga, Bi, Sb, Zr, Hf, Ti, Ta, Nb, W, Y, Gd, Tb and Sm. These elements may generate cations in water. The ion-bonded solid electrolyte material may further contain, for example, at least one halogen element selected from the group consisting of Cl, Br, I and F. These elements may generate anions in water. The ion-bonded solid electrolyte may contain at least one element selected from the group consisting of Gd, Ca, Zr and Y, at least one element selected from the group consisting of Cl, Br, I and F, and Li. The ion-bonded solid electrolyte may contain Li and Y, and at least one element selected from the group consisting of Cl, Br, I and F. More specifically, the ionically bonded solid electrolyte may contain Li, Y, Cl, and Br, or may contain Li, Ca, Y, Gd, Cl, and Br, or may contain Li, Zr, Y, and Cl. 3 YBr 2 Cl 4 , Li 2.8 Ca 0.1 Y 0.5 Gd 0.5 Br 2 Cl 4 , and Li 2.5 Y 0.5 Zr 0.5 Cl 6 It may be at least one of the above.
[0062] The ionically bonded solid electrolyte may be a halide solid electrolyte. The halide solid electrolyte has excellent ion conductivity. Examples of the halide solid electrolyte include those represented by the formula (A): Li α M β X γ (A) It may have a composition represented by the following. Here, α, β, and γ are each independently a value greater than 0, M is at least one selected from the group consisting of metal elements other than Li and metalloid elements, and X is at least one selected from the group consisting of Cl, Br, and I. Note that the "metalloid element" may be at least one selected from the group consisting of B, Si, Ge, As, Sb, and Te. Also, the "metal element" may include (i) all elements contained in Groups 1 to 12 of the periodic table (excluding hydrogen) and (ii) all elements contained in Groups 13 to 16 of the periodic table (excluding B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se). The metal element can form an inorganic compound with a halide ion and become a cation.
[0063] In formula (A), M may contain Y (i.e., yttrium). The halide solid electrolyte containing Y is Li a Me b Y c X 6 (where a + mb + 3c = 6, c > 0, Me is at least one selected from the group consisting of metal elements and metalloid elements other than Li and Y, and m is the valence of Me) may have a composition represented by the following. Me may be at least one selected from the group consisting of, for example, Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, and Nb.
[0064] The halide solid electrolyte may have a composition represented by formula (A1): Li 6-3d Y d X 6 In formula (A1), X is one or more elements selected from the group consisting of Cl, Br, and I. d may satisfy 0 < d < 2, or d may be 1. The halide solid electrolyte may have a composition represented by formula (A2): Li 3-3δ Y 1+δ Cl 6It may have a composition represented by. In formula (A2), 0 < δ ≦ 0.15 may be satisfied. The halide solid electrolyte has the formula (A3): Li 3-3δ Y 1+δ Br 6 It may have a composition represented by. In formula (A3), 0 < δ ≦ 0.25 may be satisfied. The halide solid electrolyte has the formula (A4): Li 3-3δ+a Y 1+δ-a Me a Cl 6-x-y Br x I y It may have a composition represented by. In formula (A4), Me may be at least one selected from the group consisting of Mg, Ca, Sr, Ba, and Zn. In formula (A4), for example, -1 < δ < 2, 0 < a < 3, 0 < (3 - 3δ + a), 0 < (1 + δ - a), 0 ≦ x ≦ 6, 0 ≦ y ≦ 6, and (x + y) ≦ 6 are satisfied. The halide solid electrolyte has the formula (A5): Li 3-3δ Y 1+δ-a Me a Cl 6-x-y Br x I y It may have a composition represented by. In formula (A5), Me may be at least one selected from the group consisting of Al, Sc, Ga, and Bi. In formula (A5), -1 < δ < 1, 0 < a < 2, 0 < (1 + δ - a), 0 ≦ x ≦ 6, 0 ≦ y ≦ 6, and (x + y) ≦ 6 may be satisfied. The halide solid electrolyte has the formula (A6): Li 3-3δ-a Y 1+δ-a Me a Cl 6-x-y Br x I y It may have a composition represented by. In formula (A6), Me may be at least one selected from the group consisting of Zr, Hf, and Ti. In formula (A6), -1 < δ < 1, 0 < a < 1.5, 0 < (3 - 3δ - a), 0 < (1 + δ - a), 0 ≦ x ≦ 6, 0 ≦ y ≦ 6, and (x + y) ≦ 6 may be satisfied. The halide solid electrolyte has the formula (A7): Li 3-3δ-2a Y 1+δ-a Me a Cl 6-x-y Brx I y In formula (A7), Me may be at least one selected from the group consisting of Ta and Nb. In formula (A7), -1<δ<1, 0 <a<1.2、0<(3-3δ-2a)、0<(1+δ-a)、0≦x≦6、0≦y≦6、かつ、(x+y)≦6であってもよい。
[0065] The ionically bonded solid electrolyte may be a complex hydride solid electrolyte. The complex hydride solid electrolyte may be composed of Li ions and complex ions containing H. The complex ion containing H may have, for example, an element M containing at least one of a nonmetallic element, a semimetallic element, and a metallic element, and H bonded to the element M. In addition, the complex ion containing H may have the element M as a central element and H surrounding the element M bonded to each other via a covalent bond. In addition, the complex ion containing H may be (M m H n ) α- In this case, m is any positive number, and n and α can be any positive number depending on m and the valence of element M. Element M may be a nonmetallic element or a metallic element capable of forming a complex ion. For example, element M may contain at least one of B, C, and N as a nonmetallic element, or may contain B. Also, for example, element M may contain at least one of Al, Ni, and Fe as a metallic element. In particular, when the complex ion contains B, or contains C and B, higher ionic conductivity is likely to be ensured. Specific examples of complex ions containing H include (CB 9 H 10 ) - , (C.B. 11 H 12 ) - , (B 10 H 10 ) 2- , (B 12 H 12 ) 2- , (BH 4 ) - , (NH 2 ) - , (AlH 4 ) -, and combinations thereof. In particular, (CB 9 H 10 ) - , (C.B. 11 H 12 ) - In other words, the complex hydride solid electrolyte may contain Li, C, B, and H.
[0066] The positive electrode active material layer 10 may or may not contain a liquid electrolyte (electrolytic solution). The electrolytic solution is a liquid containing lithium ions as carrier ions. The electrolytic solution may be an aqueous electrolytic solution or a non-aqueous electrolytic solution. The composition of the electrolytic solution may be the same as that of a known solution. The electrolytic solution may be a solution in which a lithium salt is dissolved in water or a non-aqueous solvent. Examples of the non-aqueous solvent include various carbonate-based solvents. Examples of the lithium salt include lithium amide salt and LiPF 6 etc.
[0067] 1.3.1.3 Conductive additives Examples of the conductive assistant that may be included in the positive electrode active material layer 10 include carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); and metal materials such as nickel, titanium, aluminum, and stainless steel. The conductive assistant may be, for example, particulate or fibrous, and the size thereof is not particularly limited. Only one type of conductive assistant may be used alone, or two or more types may be used in combination.
[0068] 1.3.1.4 Binders Examples of binders that can be included in the positive electrode active material layer 10 include butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, acrylate butadiene rubber (ABR)-based binders, styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVdF)-based binders, polytetrafluoroethylene (PTFE)-based binders, polyimide (PI)-based binders, etc. Only one type of binder may be used alone, or two or more types may be used in combination.
[0069] 1.3.1.5 Other The positive electrode active material layer 10 may contain various additives in addition to the above components, such as a dispersant and a lubricant.
[0070] 1.3.2 Electrolyte layer The electrolyte layer 20 is disposed between the positive electrode active material layer 10 and the negative electrode active material layer 30. The electrolyte layer 20 may contain one or both of a solid electrolyte and an electrolytic solution. The electrolyte layer 20 may further contain a binder or the like. The content of the electrolyte and the binder or the like in the electrolyte layer 20 is not particularly limited. Alternatively, the electrolyte layer 20 may have a separator or the like for holding the electrolyte and preventing contact between the positive electrode active material layer 10 and the negative electrode active material layer 30. The thickness of the electrolyte layer 20 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.
[0071] The electrolyte layer 20 may be composed of one layer or may be composed of multiple layers. For example, the electrolyte layer 20 may include a first layer disposed on the positive electrode active material layer 10 side and a second layer disposed on the negative electrode active material layer 30 side, and the first layer may include the first electrolyte, and the second layer may include the second electrolyte. The first electrolyte and the second electrolyte may be different from each other. The first electrolyte and the second electrolyte may each be at least one selected from the above-mentioned oxide solid electrolyte, sulfide solid electrolyte, and ionic solid electrolyte. For example, the first layer may include an ionic solid electrolyte, and the second layer may include at least one of an ionic solid electrolyte and a sulfide solid electrolyte.
[0072] The electrolyte contained in the electrolyte layer 20 may be appropriately selected from those exemplified as electrolytes that may be contained in the positive electrode active material layer 10 (solid electrolytes and / or liquid electrolytes). The binder that may be contained in the electrolyte layer 20 may also be appropriately selected from those exemplified as binders that may be contained in the positive electrode active material layer 10. Each of the electrolytes and binders may be used alone or in combination of two or more. The separator may be a known one, and examples thereof include those made of resins such as polyethylene (PE), polypropylene (PP), polyester, and polyamide. The separator may have a single layer structure or a multilayer structure. Examples of the multilayer separator include a separator with a two-layer structure of PE / PP, or a separator with a three-layer structure of PP / PE / PP or PE / PP / PE. The separator may be made of a nonwoven fabric such as a cellulose nonwoven fabric, a resin nonwoven fabric, or a glass fiber nonwoven fabric.
[0073] 1.3.3 Negative electrode active material layer The negative electrode active material layer 30 includes at least a negative electrode active material. The negative electrode active material layer 30 may also include an electrolyte, a conductive assistant, a binder, various additives, and the like. The content of each component in the negative electrode active material layer 30 may be appropriately determined according to the intended battery performance. For example, the content of the negative electrode active material may be 40% by mass or more, 50% by mass or more, 60% by mass or more, or 70% by mass or more, or 100% by mass or less, less than 100% by mass, 95% by mass or less, or 90% by mass or less, based on the entire solid content of the negative electrode active material layer 30 being 100% by volume. Alternatively, the negative electrode active material and optionally the electrolyte, the conductive assistant, and the binder may be included in a total amount of 85% by volume or more, 90% by volume or more, or 95% by volume or more, based on the entire negative electrode active material layer 30 being 100% by volume, and the remainder may be voids or other components. The shape of the negative electrode active material layer 30 is not particularly limited, and may be, for example, a sheet having a substantially flat surface. The thickness of the negative electrode active material layer 30 is not particularly limited, and may be, for example, 0.1 μm or more, 1 μm or more, 10 μm or more, or 30 μm or more, and may be 2 mm or less, 1 mm or less, 500 μm or less, or 100 μm or less.
[0074] The negative electrode active material may be any of those known as negative electrode active materials for batteries. Of the known active materials, various materials may be used that have a potential (charge / discharge potential) for absorbing and releasing lithium ions that is lower than the above-mentioned positive electrode active material. For example, silicon-based active materials such as Si, Si alloys, and silicon oxide; carbon-based active materials such as graphite and hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium, lithium alloys, and the like may be used. Among them, when the negative electrode active material layer 30 contains Si as the negative electrode active material, the performance of the solid-state battery 100 is likely to be improved. Only one type of negative electrode active material may be used alone, or two or more types may be used in combination. The shape of the negative electrode active material may be any shape that is common as a negative electrode active material for batteries. For example, the negative electrode active material may be in the form of particles. The negative electrode active material particles may be primary particles, or may be secondary particles formed by agglomeration of a plurality of primary particles. The average particle diameter (D50) of the negative electrode active material particles may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. Alternatively, the negative electrode active material may be in the form of a sheet (foil or film) such as a lithium foil. That is, the negative electrode active material layer 30 may be made of a sheet of the negative electrode active material.
[0075] Examples of the electrolyte that can be contained in the negative electrode active material layer 30 include the above-mentioned solid electrolyte, electrolytic solution, or a combination thereof. The conductive assistant that can be contained in the negative electrode active material layer 30 may be appropriately selected from, for example, those exemplified as the conductive assistant that can be contained in the above-mentioned positive electrode active material layer. The binder that can be contained in the negative electrode active material layer 30 may be appropriately selected from, for example, those exemplified as the binder that can be contained in the above-mentioned positive electrode active material layer. Each of the electrolyte, conductive assistant, and binder may be used alone or in combination of two or more kinds.
[0076] 1.3.4 Positive electrode current collector As shown in FIG. 3, the solid-state battery 100 may include a positive electrode current collector 40 in contact with the positive electrode active material layer 10. The positive electrode current collector 40 may be any of those commonly used as a positive electrode current collector for a battery. The positive electrode current collector 40 may have at least one shape selected from a foil shape, a plate shape, a mesh shape, a punched metal shape, and a foam. The positive electrode current collector 40 may be made of a metal foil or a metal mesh. In particular, a metal foil is excellent in terms of handling and the like. The positive electrode current collector 40 may be made of a plurality of foils. Examples of metals constituting the positive electrode current collector 40 include at least one selected from Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, V, Mg, Pb, Ge, In, Sn, Zr, and stainless steel. In particular, from the viewpoint of ensuring oxidation resistance, the positive electrode current collector 40 may contain Al. The positive electrode collector 40 may have some kind of coating layer on its surface for the purpose of adjusting the resistance or the like. For example, the positive electrode collector 40 may have a carbon coating layer. The positive electrode collector 40 may be a metal foil or a substrate on which the above-mentioned metal is plated or vapor-deposited. When the positive electrode collector 40 is made of a plurality of metal foils, some kind of layer may be present between the plurality of metal foils. The thickness of the positive electrode collector 40 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.
[0077] 1.3.5 Negative electrode current collector As shown in FIG. 3, the solid-state battery 100 may include a negative electrode current collector 50 in contact with the negative electrode active material layer 30. The negative electrode current collector 50 may be any of those commonly used as a negative electrode current collector for a battery. The negative electrode current collector 50 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, or the like. The negative electrode current collector 50 may be a metal foil or a metal mesh, or may be a carbon sheet. In particular, a metal foil is excellent in terms of ease of handling. The negative electrode current collector 50 may be made of a plurality of foils or sheets. Examples of metals constituting the negative electrode current collector 50 include at least one selected from Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, V, Mg, Pb, Ge, In, Sn, Zr, and stainless steel. In particular, from the viewpoint of ensuring reduction resistance and being difficult to alloy with lithium, the negative electrode current collector 50 may contain at least one metal selected from Cu, Ni, and stainless steel. The negative electrode current collector 50 may have some kind of coating layer on its surface for the purpose of adjusting resistance, etc. For example, the negative electrode current collector 50 may have a carbon coating layer. The negative electrode current collector 50 may be an aluminum foil having a carbon coating layer. The negative electrode current collector 50 may also be a metal foil or a base material on which the above metal is plated or vapor-deposited. In addition, when the negative electrode current collector 50 is made of a plurality of metal foils, some kind of layer may be present between the plurality of metal foils. The thickness of the negative electrode current collector 50 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.
[0078] 1.3.6 Other Configurations The solid-state battery 100 may have a general battery configuration in addition to the above configuration. For example, a tab, a terminal, etc. The solid-state battery 100 may have each of the above configurations housed inside an exterior body. Any known exterior body for a battery can be used as the exterior body. In addition, a plurality of solid-state batteries 100 may be electrically connected in any way and stacked in any way to form an assembled battery. In this case, the assembled battery may be housed inside a known battery case. Examples of the shape of the solid-state battery 100 include a coin type, a laminate type, a cylindrical type, and a square type.
[0079] The solid-state battery 100 can be manufactured by applying a known method, except for using the specific positive electrode active material described above. For example, it can be manufactured as follows. However, the manufacturing method of the solid-state battery 100 is not limited to the following method, and each layer may be formed by, for example, dry molding or the like. (1) The positive electrode active material constituting the positive electrode active material layer is dispersed in a solvent to obtain a positive electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used. The positive electrode layer slurry is applied to the surface of a positive electrode current collector using a doctor blade or the like, and then dried to form a positive electrode active material layer on the surface of the positive electrode current collector, thereby forming a positive electrode. (2) The negative electrode active material constituting the negative electrode active material layer is dispersed in a solvent to obtain a negative electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used. The negative electrode layer slurry is applied to the surface of the negative electrode current collector using a doctor blade or the like, and then dried to form a negative electrode active material layer on the surface of the negative electrode current collector, thereby forming a negative electrode. (3) The layers are laminated so that the electrolyte layer (solid electrolyte layer or separator) is sandwiched between the negative electrode and the positive electrode to obtain a laminate having the negative electrode current collector, the negative electrode active material layer, the electrolyte layer, the positive electrode active material layer, and the positive electrode current collector in this order. Other members such as terminals are attached to the laminate as necessary. (4) The laminate is housed in a battery case, and the laminate is sealed in the battery case together with an optional electrolyte to form a solid-state battery.
[0080] 2.Second form The positive electrode active material according to the second embodiment is used in a liquid battery.
[0081] 2.1 Manufacturing method of positive electrode active material used in liquid batteries As shown in FIG. 1B, the method for producing a positive electrode active material used in a liquid battery includes the following steps: Obtaining Na-containing oxide particles having an S1:P2 type structure, and S2: Ion-exchanging at least a portion of the Na in the Na-containing oxide particles with Li to obtain Li-containing oxide particles having an O2 type structure. Here, the Na-containing oxide particles are spherical particles having an average particle size of 3.5 μm or more, and as shown in FIG. 2B, the Li-containing oxide particles are spherical particles having a hollow multi-layer structure.
[0082] 2.1.1 S1 In S1, Na-containing oxide particles having a P2 type structure are obtained. Here, the Na-containing oxide particles obtained by S1 are spherical particles having an average particle diameter of 3.5 μm or more. S1 in the second embodiment is the same as S1 in the first embodiment except that the average particle diameter of the Na-containing oxide particles is different. That is, S1 in the second embodiment may include the above S1-1, S1-2, and S1-3. For example, by using precursor particles that have an average particle diameter of 3.5 μm or more and are spherical, Na-containing oxide particles having an average particle diameter of 3.5 μm or more are obtained. Alternatively, after producing spherical Na-containing oxide particles using precursor particles having random sizes, air flow classification, sieving, etc. may be performed to recover spherical Na-containing oxide particles having an average particle diameter of 3.5 μm or more.
[0083] As described above, the Na-containing oxide particles obtained by S1 in the second embodiment may be the same as the Na-containing oxide particles obtained by S1 in the first embodiment, except for the difference in average particle size. That is, the Na-containing oxide particles have at least a P2 type structure (belonging to the space group P63mc) as a crystal structure. The Na-containing oxide particles may have a P2 type structure and a crystal structure other than the P2 type structure. Examples of the crystal structure other than the P2 type structure include various crystal structures formed when Na is desorbed from the P2 type structure. The Na-containing oxide particles may have a P2 type structure as a main phase. In addition, the Na-containing oxide particles may contain, for example, at least one element selected from Mn, Ni, and Co, Na, and O as constituent elements. In particular, when the constituent elements include at least Na, Mn, at least one of Ni and Co, and O, and especially when the constituent elements include at least Na, Mn, Ni, Co, and O, the performance of the positive electrode active material obtained through S2 described below tends to be further improved. c Mn x-p Ni y-q Co z-r M p+q+r O 2It may have a chemical composition represented by the following. Here, 0 < c ≤ 1.00, x + y + z = 1, and 0 ≤ p + q + r < 0.17. Also, M is at least one element selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W. When the Na-containing oxide particles have such a chemical composition, the P2-type structure is more likely to be maintained. In the above chemical composition, c may be greater than 0, 0.10 or more, 0.20 or more, 0.30 or more, 0.40 or more, 0.50 or more, or 0.60 or more, and may be 1.00 or less, 0.90 or less, 0.80 or less, or 0.70 or less. x is 0 or more, may be 0.10 or more, 0.20 or more, 0.30 or more, 0.40 or more, or 0.50 or more, and is 1.00 or less, may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, or 0.50 or less. Also, y is 0 or more, may be 0.10 or more or 0.20 or more, and is 1.00 or less, may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, 0.30 or less, or 0.20 or less. Also, z is 0 or more, may be 0.10 or more, 0.20 or more, or 0.30 or more, and is 1.00 or less, may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, or 0.30 or less. The contribution of element M to charge and discharge is small. In this regard, in the above chemical composition, since p + q + r is less than 0.17, it is easy to ensure a high charge and discharge capacity. p + q + r may be 0.16 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, or 0.10 or less. On the other hand, when element M is included, the P2-type structure and the O2-type structure are likely to be stabilized. In the above chemical composition, p + q + r is 0 or more, may be 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, or 0.10 or more. The composition of O is approximately 2, but is not necessarily exactly 2.0 and is indefinite.
[0084] The average particle diameter of the Na-containing oxide particles is 3.5 μm or more. The average particle diameter may be 3.5 μm or more and 20.0 μm or less, 3.5 μm or more and 10.0 μm or less, or 3.5 μm or more and 5.0 μm or less. When the average particle diameter of the Na-containing oxide particles is 3.5 μm or more, the Li-containing oxide particles obtained through S2 described later have a hollow multilayer structure.
[0085] 2.1.2 S2 In S2, at least a part of the Na in the Na-containing oxide particles obtained in S1 is ion-exchanged with Li to obtain Li-containing oxide particles having an O2 type structure. Here, the Li-containing oxide particles obtained in S2 are spherical particles having a hollow multi-layer structure. S2 in the second embodiment is the same as S2 in the first embodiment, except that the average particle size of the Na-containing oxide particles is different.
[0086] As described above, in S2, at least a part of Na in the spherical Na-containing oxide particles is ion-exchanged with Li, and voids are generated inside the particles due to shrinkage during ion exchange. As described above, when the size of the Na-containing oxide particles is large, cracks are generated in the circumferential direction inside the particles due to the shrinkage, resulting in a large number of "shells" and a hollow multilayer structure.
[0087] By the above method, Li-containing oxide particles having an O2 type structure, a hollow multi-layer structure, spherical particles, and an average particle size of 3.5 μm or more can be obtained. The Li-containing oxide particles can be used as a positive electrode active material for liquid batteries.
[0088] 2.2 Positive electrode active materials used in liquid batteries The positive electrode active material used in the liquid battery according to the second embodiment includes Li-containing oxide particles. Here, the Li-containing oxide particles have an O2 type structure. As shown in FIG. 2B, the Li-containing oxide particles are spherical particles having a hollow multi-layer structure. The Li-containing oxide particles have an average particle size of 3.5 μm or more.
[0089] 2.2.1 Crystal structure, crystallites and chemical composition The crystal structure, crystallites, and chemical composition of the Li-containing oxide particles according to the second embodiment may be the same as those of the first embodiment. That is, the Li-containing oxide particles according to the second embodiment may have an O2 type structure and may have other crystal structures in addition to the O2 type structure. The Li-containing oxide particles according to the second embodiment may be polycrystalline having a plurality of crystallites. The Li-containing oxide particles according to the second embodiment may contain, for example, at least one element selected from Mn, Ni, and Co, Li, and O as constituent elements. The Li-containing oxide particles are particularly likely to achieve higher performance when they contain at least Li, Mn, one or both of Ni and Co, and O as constituent elements, and particularly when they contain at least Li, Mn, Ni, Co, and O as constituent elements. The Li-containing oxide particles are Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O 2(Here, 0 < a ≤ 1.00, 0 ≤ b ≤ 0.20, x + y + z = 1, and 0 ≤ p + q + r < 0.17, and the element M is at least one selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W.) It may have a chemical composition represented by this. When the Li-containing oxide particles have such a chemical composition, the O2-type structure is likely to be maintained. In the above chemical composition, a is greater than 0, and may be 0.10 or more, 0.20 or more, 0.30 or more, 0.40 or more, 0.50 or more, or 0.60 or more, and is at most 1.00, and may be 0.90 or less, 0.80 or less, or 0.70 or less. In the above chemical composition, b is 0 or more, and may be 0.01 or more, 0.02 or more, or 0.03 or more, and is at most 0.20, and may be 0.15 or less, or 0.10 or less. Also, x is 0 or more, and may be 0.10 or more, 0.20 or more, 0.30 or more, 0.40 or more, or 0.50 or more, and is at most 1.00, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, or 0.50 or less. Also, y is 0 or more, and may be 0.10 or more, or 0.20 or more, and is at most 1.00, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, 0.30 or less, or 0.20 or less. Also, z is 0 or more, and may be 0.10 or more, 0.20 or more, or 0.30 or more, and is at most 1.00, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, or 0.30 or less. The element M has little contribution to charge and discharge. In this regard, in the above chemical composition, since p + q + r is less than 0.17, a high charge and discharge capacity is likely to be ensured. p + q + r may be 0.16 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, or 0.10 or less. On the other hand, when the element M is included, the O2-type structure is likely to be stabilized. In the above chemical composition, p + q + r is 0 or more, and may be 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, or 0.10 or more.)The composition of O is approximately 2, but is not necessarily exactly 2.0 and is variable.
[0090] 2.2.2 Hollow multilayer structure The Li-containing oxide particles according to the second embodiment have a hollow multi-layer structure. As shown in FIG. 2B, the "hollow multi-layer structure" means a structure having an outer shell 1a and at least one inner shell 1b or solid portion 1c in the cross-sectional shape of the particle. As shown in FIG. 2C, the solid portion 1c may not exist and may be a gap. The Li-containing oxide particles according to the second embodiment may have multiple shells 1a and 1b, or may have an outer shell 1a and a solid portion 1c. In this case, a gap may exist between at least one shell and another shell or between a shell and a solid portion. When the Li-containing oxide particles have multiple shells 1a and 1b, the outside and inside of each shell may come into contact with a liquid, so that the contact area between the Li-containing oxide particles and the liquid is likely to increase. For example, when the electrolyte is distributed inside the Li-containing oxide particles, the contact area between the particles and the electrolyte is likely to increase. In addition, "having multiple shells" means that another shell exists inside one shell. Here, one shell and another shell may be in partial contact with each other or may be partially bonded to each other, but even if there is a gap between one shell and another shell located further inside along the circumferential direction, if 50% or more of the inner circumference of one shell is bonded to the outer circumference of the other shell located further inside, the one shell and the other shell are not regarded as separate shells (multi-layer), but are regarded as constituting one shell (single layer).
[0091] In the Li-containing oxide particle according to the second embodiment, the surface of the outer shell 1a may be composed of, for example, a plurality of crystallites. In the Li-containing oxide particle, the outer shell 1a may be composed of a plurality of crystallites arranged along the outer periphery of the particle. The size of the crystallites constituting the outer shell 1a may be large or small, but the smaller the crystallite size, the more grain boundaries there are on the particle surface, and the more advantageous effects are likely to be exhibited. The crystallites constituting the outer shell 1a may have a first surface exposed on the particle surface, and the first surface may be planar. The size of the crystallites is as described above. The outer shape (outer peripheral shape) of the outer shell 1a is spherical as described above. On the other hand, the inner shape (inner peripheral shape) of the outer shell 1a is not particularly limited and may be a shape corresponding to the outer shape. However, the outer shape and the inner shape of the outer shell 1a do not need to be parallel to each other. Both the outer shape and the inner shape of the outer shell may have irregularities. The outer shell 1a may have voids or gaps. That is, the crystallites constituting the outer shell 1a may have defects such as voids and gaps. Furthermore, the outer shell 1a may have a thickness. The thickness of the outer shell 1a may be, for example, 5% to 40% or 5% to 30% of the diameter (circle equivalent diameter in the cross-sectional shape) of the Li-containing oxide particle. The size (porosity) of the voids present inside the outer shell 1a is not particularly limited. The outer shape (outer peripheral shape) of the inner shell 1b may be a shape corresponding to the inner peripheral shape of the outer shell 1a, or may be a shape different from the inner peripheral shape of the outer shell 1a. The inner shape (inner peripheral shape) of the inner shell 1b is not particularly limited and may be a shape corresponding to the outer shape. The outer shape and the inner shape of the inner shell 1b do not need to be parallel to each other. Both the outer shape and the inner shape of the inner shell 1b may have unevenness. Furthermore, the inner shell 1b may have voids and gaps. That is, the crystallites constituting the inner shell 1b may have defects such as voids and gaps. Furthermore, the inner shell 1b may have a thickness. The thickness of the inner shell 1b may be, for example, 5% to 40% or 5% to 30% of the diameter of the Li-containing oxide particle (equivalent circle diameter in the cross-sectional shape). The shape and size of the gap between the outer shell 1a and the inner shell 1b, and the shape and size of the solid portion 1c or gap inside the inner shell 1b are not particularly limited. In addition, the porosity of the particle as a whole is not particularly limited.
[0092] As shown in FIG. 2B, in the Li-containing oxide particle according to the second embodiment, in the cross-sectional structure, voids exist along the inner wall of the outer shell 1a. The voids may exist continuously around the entire circumference of the inner wall of the outer shell 1a, or may exist continuously or intermittently along a part of the inner wall of the outer shell 1a. For example, the voids may exist over 50% or more of the entire inner circumference of the outer shell 1a. The size of the voids is not particularly limited. As described above, the shell may have liquid permeability, so that the liquid that has permeated from the outside of the particle to the inside of the particle through the shell may fill the voids existing along the inner wall of the shell and come into contact with the inner wall of the shell. That is, when voids exist along the inner wall of the shell, the contact area between the particle and the liquid is more likely to increase than when there are no voids. For example, when the electrolyte solution is distributed inside the Li-containing oxide particle, the contact area between the particle and the electrolyte solution is more likely to increase.
[0093] 2B, the Li-containing oxide particle according to the second embodiment can be said to have a core-shell structure. That is, the Li-containing oxide particle according to one embodiment can have a shell (outer shell) and a core (inner shell or solid portion, and voids) disposed inside the shell.
[0094] 2.2.3 Spherical particles As shown in FIG. 2B, the Li-containing oxide particles according to the second embodiment are spherical particles. As described above, the spherical Li-containing oxide particles have the advantage that the growth of crystallites is easily suppressed and the crystallites are easily small, compared with non-spherical Li-containing oxide particles. That is, when the Li-containing oxide particles are spherical, the reaction resistance is reduced due to the reduction in the crystallite size, and the internal diffusion resistance is easily reduced. Furthermore, it is considered that the degree of curvature is reduced by the spheroidization, and when applied to a positive electrode active material layer, the lithium ion conduction resistance in the layer is reduced. As a result, the spherical Li-containing oxide particles tend to have lower resistance and excellent rate characteristics, compared with non-spherical Li-containing oxide particles.
[0095] 2.2.4 Average particle size The Li-containing oxide particles according to the second embodiment have an average particle diameter of 3.5 μm or more. The average particle diameter of the Li-containing oxide particles may be 3.5 μm or more and 20.0 μm or less, 3.5 μm or more and 10.0 μm or less, or 3.5 μm or more and 5.0 μm or less. As described above, when the average particle diameter of the Li-containing oxide particles is 3.5 μm or more, the Li-containing oxide particles have a hollow multilayer structure, and when applied to a liquid battery, the Li-containing oxide particles have excellent rate characteristics.
[0096] 2.2.5 Specific surface area The specific surface area of the Li-containing oxide particles according to the second embodiment is not particularly limited. However, when it is assumed that the particles are used as a positive electrode active material of a liquid battery, it is considered that the larger the specific surface area of the Li-containing oxide particles, the more the contact interface with the electrolyte increases, and the easier it is to ensure an ion conduction path. In this regard, when the Li-containing oxide particles have a hollow multilayer structure, are spherical particles, and have an average particle size of 3.5 μm or more, the Li-containing oxide particles have an average particle size of 4.5 μm or more. 2 The Li-containing oxide particles may have a specific surface area of 4.5 m / g or more. 2 / g or more 10.0m 2 / g or less, 4.5m 2 / g or more 8.0m 2 / g or less, or 4.5m 2 / g or more 6.5m 2 / g or less.
[0097] 2.2.6 Supplementary Information The positive electrode active material according to the second embodiment may be composed of only the Li-containing oxide particles, as in the first embodiment, or may contain other positive electrode active materials (other positive electrode active materials) together with the Li-containing oxide particles. From the viewpoint of further enhancing the effect of the technology of the present disclosure, the ratio of other positive electrode active materials in the entire positive electrode active material may be small. For example, the content of the Li-containing oxide particles may be 50% by mass or more and 100% by mass or less, 60% by mass or more and 100% by mass or less, 70% by mass or more and 100% by mass or less, 80% by mass or more and 100% by mass or less, 90% by mass or more and 100% by mass or less, 95% by mass or more and 100% by mass or less, or 99% by mass or more and 100% by mass or less, based on the entire positive electrode active material being 100% by mass.
[0098] 2.3 Liquid batteries The positive electrode active material according to the second embodiment is used as a positive electrode active material for a liquid battery. The term "liquid battery" refers to a battery containing a liquid electrolyte (electrolytic solution). The electrolyte contained in the liquid battery may be a liquid electrolyte or a combination of a liquid electrolyte and a solid electrolyte. FIG. 3 shows a schematic configuration of a liquid battery according to an embodiment. As shown in FIG. 3, a liquid battery 100 according to an embodiment has a positive electrode active material layer 10, an electrolyte layer 20, and a negative electrode active material layer 30. Here, the positive electrode active material layer 10 contains the positive electrode active material according to the second embodiment. The positive electrode active material layer 10 also contains a liquid electrolyte.
[0099] The positive electrode active material layer 10, electrolyte layer 20 and negative electrode active material layer 30 provided in the liquid battery 100 may be similar to those provided in the solid battery 100, except that they have the positive electrode active material according to the second embodiment as the positive electrode active material and contain a liquid electrolyte as the electrolyte. The configuration of the liquid battery 100 is self-evident, so a detailed description will be omitted here.
[0100] 3. Vehicles The solid-state battery or liquid-based battery of the present disclosure can be suitably used in at least one type of vehicle selected from, for example, a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), and an electric vehicle (BEV). That is, the technology of the present disclosure also has an aspect of a vehicle having one or both of the solid-state battery and the liquid-based battery of the present disclosure.
[0101] 4.Effects As described above, the positive electrode active material according to the first embodiment has low resistance when applied to a solid-state battery, and the positive electrode active material according to the second embodiment has excellent rate characteristics when applied to a liquid battery. EXAMPLES
[0102] As described above, one embodiment of the manufacturing method of the positive electrode active material, the positive electrode active material, the battery, etc. has been described, but the technology of the present disclosure can be modified in various ways other than the above embodiment without departing from the gist of the technology. The technology of the present disclosure will be described in more detail below while showing examples, but the technology of the present disclosure is not limited to the following examples.
[0103] 1. Preparation of Positive Electrode Active Material 1.1 Cathode active material A 1.1.1 Preparation of precursor particles a1 (1) MnSO 4 5H 2 O, NiSO 4 6H 2 O, CoSO 4 7H 2 The first solution was obtained by weighing out the desired composition ratio of O and dissolving it in distilled water to a concentration of 1.2 mol / L. 2 CO 3 was dissolved in distilled water to a concentration of 1.2 mol / L to obtain a second solution. (2) 1000 mL of pure water was placed in a reaction vessel (with a baffle plate), and 500 mL of the first solution and 500 mL of the second solution were each added dropwise at a rate of about 4 mL / min. (3) After the dropwise addition was completed, the mixture was stirred at room temperature at a stirring speed of 150 rpm for 1 hour to obtain a product. (4) The product was washed with pure water, subjected to solid-liquid separation using a centrifuge, and the precipitate was collected. (5) The obtained precipitate was dried overnight at 120°C, crushed in a mortar, and then separated into coarse particles a1-1 and fine particles a1-2 by air classification. Here, both the coarse particles a1-1 and the fine particles a1-2 are composite salts containing Mn, Ni, and Co. The coarse particles a1-1 had an average particle diameter D50 of 4.0 μm and were spherical particles. The fine particles a1-2 had an average particle diameter D50 of 1.8 μm and were spherical particles. (6) As the precursor particles a1, coarse particles a1-1 were used.
[0104] 1.1.2 Preparation of composite particle a2 (1) Na to 1150g / L 2 CO 3 After weighing out and distilled water, stir using a stirrer until completely dissolved. 2 CO 3 An aqueous solution was prepared. (2) The above Na 2 CO 3 The aqueous solution and the above-mentioned precursor particles a1 are mixed and then calcined to obtain a composition of Na 0.7 Mn 0.5 Ni 0.2 Co 0.3 O 2 The components were weighed and mixed so as to obtain a slurry. (3) The above slurry was air-dried by spray drying to obtain composite particles a2. Specifically, a spray dryer DL410 was used, with a slurry delivery rate of 30 mL / min, an inlet temperature of 200°C, and a circulating air volume of 0.8 m 3 The above slurry was dried by air flow under the conditions of 0.3 MPa spraying speed and 0.5 sieve / min, and the surface of the precursor particles a1 was coated with Na 2 CO 3 In the composite particle a2, 77% by area of the surface of the precursor particle a1 was covered with Na 2 CO 3 It was covered with.
[0105] 1.1.3 Firing of composite particles a2 The composite particles a2 were placed in an alumina crucible and sintered in an air atmosphere to obtain Na-containing oxide particles a3 having a P2 type structure under the following sintering conditions (1) to (7). (1) The alumina crucible containing the composite particles a2 is placed in a heating furnace in an air atmosphere. (2) The temperature inside the heating furnace is raised from room temperature (25°C) to 600°C in 115 minutes. (3) The temperature in the heating furnace is kept at 600°C for 360 minutes to perform pre-baking. (4) After preliminary firing, the temperature inside the heating furnace is raised from 600°C to 900°C in 100 minutes. (5) The temperature in the heating furnace is kept at 900°C for 60 minutes to perform the main firing. (6) After the main firing, the temperature in the heating furnace is lowered from 900°C to 250°C in 120 minutes. (7) Remove the alumina crucible from the heating furnace at 250°C and allow it to cool in a dry atmosphere outside the furnace until it reaches 25°C in 10 minutes.
[0106] The calcined product after cooling was pulverized in a mortar under a dry atmosphere to obtain Na-containing oxide particles a3 having a P2 type structure (P2 type particles a3). The P2 type particles a3 had an average particle diameter D50 of 3.2 μm and were spherical particles.
[0107] 1.1.4 Ion exchange (1) LiNO 3 and LiCl were weighed out to have a molar ratio of 50:50, and mixed with the above P2 type particles a3 in a molar ratio that was 10 times the minimum Li amount required for ion exchange to obtain a mixture. (2) Using an alumina crucible, ion exchange was carried out in air at 280°C for 1 hour to obtain a product containing Li-containing oxide. (3) The salt remaining in the product was washed with pure water, and solid-liquid separation was performed by vacuum filtration to obtain a precipitate. (4) The obtained precipitate was dried overnight at 120° C. to obtain a positive electrode active material A.
[0108] 1.2 Cathode active material B 1.2.1 Preparation of precursor particles b1 As the precursor particles b1, the above-mentioned fine particles a1-2 were used.
[0109] 1.2.2 Preparation and sintering of composite particles b2 Composite particles b2 were prepared in the same manner as above, except that precursor particles b1 were used instead of precursor particles a1, and the composite particles b2 were fired to obtain Na-containing oxide particles b3 having a P2 type structure (P2 type particles b3). The P2 type particles b3 had an average particle diameter D50 of 1.8 μm and were spherical particles.
[0110] 1.2.3 Ion exchange A positive electrode active material B was obtained by carrying out ion exchange in the same manner as above, except that the P2 type particles b3 were used instead of the P2 type particles a3.
[0111] 1.3 Cathode active material C 1.3.1 Preparation of precursor particles c1 (1) MnSO 4 5H 2 O, NiSO 4 6H 2 O, CoSO 4 7H 2 The first solution was obtained by weighing out the desired composition ratio of O and dissolving it in distilled water to a concentration of 2 mol / L. 2 CO 3 was dissolved in distilled water to a concentration of 2 mol / L to obtain a second solution. (2) 1000 mL of pure water was placed in a reaction vessel (with a baffle plate), and 900 mL of the first solution and 900 mL of the second solution were each added dropwise at a rate of about 4 mL / min. (3) After the dropwise addition was completed, the mixture was stirred at room temperature at a stirring speed of 150 rpm for 1 hour to obtain a product. (4) The product was washed with pure water, subjected to solid-liquid separation using a centrifuge, and the precipitate was collected. (5) The obtained precipitate was dried overnight at 120°C, crushed in a mortar, and then separated into coarse particles c1-1 and fine particles c1-2 by air classification. Here, both the coarse particles c1-1 and the fine particles c1-2 are composite salts containing Mn, Ni, and Co. The coarse particles c1-1 had an average particle diameter D50 of 4.8 μm and were spherical particles. (6) Coarse particles c1-1 were used as precursor particles c1.
[0112] 1.3.2 Preparation and sintering of composite particles c2 Composite particles c2 were prepared in the same manner as above, except that precursor particles c1 were used instead of precursor particles a1, and the composite particles c2 were calcined to obtain Na-containing oxide particles c3 having a P2 type structure (P2 type particles c3). The P2 type particles c3 had an average particle diameter D50 of 4.3 μm and were spherical particles.
[0113] 1.3.3 Ion exchange A positive electrode active material C was obtained by carrying out ion exchange in the same manner as above, except that the P2 type particles c3 were used instead of the P2 type particles a3.
[0114] 1.4 Cathode active material D 1.4.1 Preparation of precursor particles d1 As the precursor particles d1, the above-mentioned fine particles a1-2 were used.
[0115] 1.4.2 Preparation of composite particle d2 Precursor particle d1 and Na 2 CO 3 And, Na 0.7 Mn 0.5 Ni 0.2 Co 0.3 O 2 The precursor particles d1 and Na were weighed to have the following composition. 2 CO 3 The precursor particles d1 and d2 were mixed in a mortar to obtain composite particles d2. In the composite particles d2, 22% by area of the surface of the precursor particles d1 was Na 2 CO 3 It was covered with.
[0116] 1.4.3 Sintering of composite particles d2 The composite particles d2 were calcined in the same manner as above, except that the composite particles a2 were replaced with the composite particles d2, to obtain Na-containing oxide particles d3 having a P2 type structure (P2 type particles d3). The P2 type particles d3 had an average particle diameter D50 of 1.3 μm and were plate-shaped particles.
[0117] 1.4.4 Ion exchange A positive electrode active material D was obtained by carrying out ion exchange in the same manner as above, except that the P2 type particles d3 were used instead of the P2 type particles a3.
[0118] 2. Evaluation of positive electrode active material 2.1 Elemental analysis and crystal structure identification Elemental analysis was performed on each of the positive electrode active materials A to D, and it was found that the target composition was obtained. Furthermore, X-ray diffraction measurements were performed, and it was found that each of the positive electrode active materials A to D had an O2 type structure.
[0119] 2.2 Measurement of average particle size and specific surface area The average particle diameter D50 and BET specific surface area were measured for each of the positive electrode active materials A to D. The average particle diameter D50 is the particle diameter (median diameter) at an integrated value of 50% in the volume-based particle size distribution by the laser diffraction / scattering method. The BET specific surface area was measured using a gas adsorption method. Specifically, a specific surface area / pore distribution measuring device (Micromeritics, Tristar) was used to perform the measurement by a constant volume method using nitrogen as the adsorbed gas. That is, a glass tube containing a sample was immersed in liquid nitrogen, the inside of the tube was evacuated, and then the relative pressure (=adsorption equilibrium pressure / saturated vapor pressure) was changed to measure the amount of adsorbed nitrogen. The BET specific surface area was calculated from the measured amount of adsorbed nitrogen and the relative pressure.
[0120] 2.3 Observation of shape The appearance and cross-sectional shape of the positive electrode active materials A to D were observed by SEM. Fig. 4 shows SEM images of the cross-sectional shapes. Positive electrode active material A was spherical particles having a hollow single-layer structure. Positive electrode active material B was spherical particles having a hollow single-layer structure. Positive electrode active material C was spherical particles having a hollow multi-layer structure. Positive electrode active material D was plate-shaped particles.
[0121] 3. Preparation of evaluation cells 3.1 Fabrication of solid-state battery A solid-state battery was fabricated using each of the positive electrode active materials. The fabrication procedure for the solid-state battery is as follows. (1) A positive electrode active material, a sulfide solid electrolyte A (argyrodite-type sulfide solid electrolyte), PVDF, and VGCF were weighed and mixed in a ratio (mass ratio) of positive electrode active material:sulfide solid electrolyte A:PVDF:VGCF=82.1:14.9:0.6:2.4 to obtain a positive electrode composite. (2) The negative electrode active material (Li15Si4 and simple Si), sulfide solid electrolyte B (Li2S-P2S5-LiI-LiBr), PVDF, and VGCF were weighed and mixed in a mass ratio of Li15S4:simple Si:sulfide solid electrolyte B:PVDF:VGCF=30.5:50.7:15.5:0.9:2.4 to obtain a negative electrode composite. (3) The sulfide solid electrolyte B and acrylate butadiene rubber (ABR) were weighed and mixed in a ratio of sulfide solid electrolyte B:ABR=99.4:0.6 (mass ratio) to obtain an electrolyte mixture. (4) The electrolyte mixture was placed in a Macol cylinder and pressed at 9.8 kN for 1 minute to form an electrolyte layer. Then, the positive electrode mixture was placed on one side of the electrolyte layer and pressed at 19.6 kN for 1 minute to form a positive electrode active material layer. Then, the negative electrode mixture was placed on the other side of the electrolyte layer and pressed at 58 kN for 3 minutes to form a negative electrode active material layer. Finally, current collectors were placed on both ends of each layer in the stacking direction to obtain a solid-state battery.
[0122] 3.2 Preparation of liquid battery A liquid battery was fabricated using each of the positive electrode active materials. The fabrication procedure for the liquid battery was as follows. (1) The positive electrode active material, acetylene black (AB) as a conductive additive, and polyvinylidene fluoride (PVdF) as a binder were weighed out so that the mass ratio of the positive electrode active material:AB:PVdF=85:10:5, and dispersed and mixed in N-methyl-2-pyrrolidone to obtain a positive electrode mixture slurry. The positive electrode mixture slurry was applied onto an aluminum foil and vacuum dried overnight at 120°C to obtain a positive electrode, which is a laminate of a positive electrode active material layer and a positive electrode current collector. (2) In a mixed solvent of trifluoropropylene carbonate (TFPC) and trifluoroethyl methyl carbonate (TFEMC) in a ratio of TFPC:TFEMC = 30 vol%:70 vol%, LiPF 6 was dissolved at a concentration of 1M to obtain an electrolyte solution. (3) Metallic lithium foil was prepared as the negative electrode. (4) A coin cell (CR2032) was fabricated as a liquid battery using a positive electrode, electrolyte, and negative electrode.
[0123] 4. Cell Evaluation 4.1 Measurement of discharge capacity of solid-state batteries The solid-state battery was charged and discharged in a thermostatic chamber maintained at 25°C at a voltage range of 1.8-4.6V and a 0.1C rate (1C = 220mA / g), and the discharge capacity was measured.
[0124] 4.2 Measurement of DCIR resistance of solid-state batteries The above solid-state battery was charged and discharged twice in a thermostatic chamber maintained at 25°C at a voltage range of 1.8-4.6V and a 0.1C rate (1C=220mA / g), and then the DCIR resistance was measured by applying a current equivalent to 3C for 10s at an SOC of 50%.
[0125] 4.3 Liquid batteries Each coin cell was charged and discharged in a thermostatic chamber maintained at 25° C. at a voltage range of 2.0-4.8 V and a rate of 0.1 C or 3 C (1 C=220 mA / g), and the capacity at 0.1 C and the capacity at 3 C were measured.
[0126] 5. Evaluation Results The evaluation results of the positive electrode active material are shown in Tables 1 and 2. The evaluation results of the solid-state battery are shown in Table 1. The evaluation results of the liquid battery are shown in Table 2.
[0127] [Table 1]
[0128] [Table 2]
[0129] As is clear from the results shown in Table 1, the positive electrode active materials A and B have low resistance when applied to a solid-state battery, and as is clear from the results shown in Table 2, the positive electrode active material C has excellent rate characteristics when applied to a liquid battery.
[0130] 6. Supplementary Information In the above examples, the precursor particles are obtained by coprecipitation, but the precursor particles can be obtained by other methods. In the above examples, the surface of the precursor particles is coated with a Na source by spray drying to obtain the composite particles, but the composite particles can be obtained by other methods. In the above examples, the Na-containing oxide having a P2 type structure and the Li-containing oxide having an O2 type structure are exemplified as those having a predetermined chemical composition, but the chemical composition of the Na-containing oxide and the Li-containing oxide is not limited to this. In addition, the Na-containing oxide and the Li-containing oxide may be doped with an element M other than Mn, Ni, and Co. The element M is as described in the embodiment.
[0131] 7. Summary As described above, in a positive electrode active material containing a Li-containing oxide, if the Li-containing oxide satisfies the following requirements (1) to (3), the resistance will be low when applied to a solid-state battery. (1) The Li-containing oxide particles have an O2 type structure. (2) The Li-containing oxide particles are spherical particles having a hollow single-layer structure. (3) The Li-containing oxide particles have an average particle size of 1.0 μm or more and less than 3.5 μm.
[0132] On the other hand, in a positive electrode active material containing a Li-containing oxide, if the Li-containing oxide satisfies the following requirements (4) to (6), the rate characteristics are excellent when applied to a liquid battery. (4) The Li-containing oxide particles have an O2 type structure. (5) The Li-containing oxide particles are spherical particles having a hollow multi-layer structure. (6) The Li-containing oxide particles have an average particle size of 3.5 μm or more.
[0133] Moreover, the Li-containing oxide particles satisfying the above requirements (1) to (3) and the Li-containing oxide particles satisfying the above requirements (4) to (6) can be produced depending on, for example, the size of the P2 type particles before ion exchange. [Explanation of symbols]
[0134] 100 Batteries (solid batteries, liquid batteries) 10 Cathode active material layer 20 Electrolyte layer 30 Negative electrode active material layer 40 Positive electrode current collector 50 Negative electrode current collector
Claims
1. A method for producing a positive electrode active material for use in a solid-state battery, comprising: Obtaining Na-containing oxide particles having a P2 type structure; and and ion-exchanging at least a portion of the Na in the Na-containing oxide particles with Li to obtain Li-containing oxide particles having an O2 type structure. The Na-containing oxide particles are spherical particles having an average particle size of 1.0 μm or more and less than 3.5 μm, The Li-containing oxide particles are spherical particles having a hollow single-layer structure. Manufacturing method.
2. The method according to claim 1, The Na-containing oxide particles contain, as constituent elements, at least one element selected from Mn, Ni, and Co, Na, and O. Manufacturing method.
3. A positive electrode active material for use in a solid-state battery, comprising Li-containing oxide particles, The Li-containing oxide particles have an O2 type structure, The Li-containing oxide particles are spherical particles having a hollow single-layer structure, The Li-containing oxide particles have an average particle size of 1.0 μm or more and less than 3.5 μm. Cathode active material.
4. The positive electrode active material according to claim 3, The Li-containing oxide particles are 4.5 m 2 / g or less specific surface area, Cathode active material.
5. The positive electrode active material according to claim 3, The Li-containing oxide particles contain, as constituent elements, at least one element selected from Mn, Ni, and Co, Li, and O. Cathode active material.
6. A solid-state battery having a positive electrode active material layer, an electrolyte layer, and a negative electrode active material layer, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 3 to 5, The positive electrode active material layer contains a solid electrolyte. solid state battery.
7. A method for producing a positive electrode active material for use in a liquid battery, comprising the steps of: Obtaining Na-containing oxide particles having a P2 type structure; and and ion-exchanging at least a portion of the Na in the Na-containing oxide particles with Li to obtain Li-containing oxide particles having an O2 type structure. The Na-containing oxide particles are spherical particles having an average particle size of 3.5 μm or more, The Li-containing oxide particles are spherical particles having a hollow multilayer structure. Manufacturing method.
8. The method according to claim 7, further comprising the steps of: The Na-containing oxide particles contain, as constituent elements, at least one element selected from Mn, Ni, and Co, Na, and O. Manufacturing method.
9. A positive electrode active material for use in a liquid battery, comprising Li-containing oxide particles, The Li-containing oxide particles have an O2 type structure, The Li-containing oxide particles are spherical particles having a hollow multilayer structure, The Li-containing oxide particles have an average particle size of 3.5 μm or more. Cathode active material.
10. The positive electrode active material according to claim 9 , The Li-containing oxide particles are 4.5 m 2 / g or more specific surface area, Cathode active material.
11. The positive electrode active material according to claim 9 , The Li-containing oxide particles contain, as constituent elements, at least one element selected from Mn, Ni, and Co, Li, and O. Cathode active material.
12. A liquid battery having a positive electrode active material layer, an electrolyte layer, and a negative electrode active material layer, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 9 to 11, The positive electrode active material layer contains a liquid electrolyte. Liquid battery.
Citation Information
Patent Citations
Positive electrode active material for use in nonaqueous electrolyte secondary battery and method for manufacturing it
JP2002313337A
Positive active material for lithium secondary battery, its manufacturing method, and lithium secondary battery
JP2004220898A
Positive-electrode active material for nonaqueous electrolyte secondary battery
JP2010232063A
Nonaqueous electrolyte secondary battery and method for manufacturing the same
JP2012094487A
Positive electrode active material for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery
JP2015092454A